Analisis Dampak Bullying Terhadap Interaksi Sosial Santri di Pondok Pesantren Modern Daar El- Falaah Mandalawangi - Luthfiya tusholihah; Agus Sukirno (Indonesian Journal of Educational Counseling, 2026)
Bullying is a highly detrimental and deviant behavior, as it can have serious impacts on an individual's mental development, both in adolescents and children. This research aims to (1) Identify the forms of bullying that occur at the Daar el-Falaah Modern Islamic Boarding School in Mandalawangi, (2) Determine the effects of bullying on the social interactions of students at the Daar el-Falaah Modern Islamic Boarding School in Mandalawangi. The research method employs a qualitative approach with a phenomenological design. Data collection techniques include observation, interviews with 6 students and 1 teacher (ustadz), and documentation. Data analysis uses Miles and Huberman's theory, which involves data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the types of bullying present in this Islamic boarding school are verbal bullying and behavioral bullying, which significantly affect the victims' social interactions, causing them to tend to isolate themselves Keywords: Bullying, Social Interaction, Islamic Boarding School Students